2006
DOI: 10.1590/s1415-47572006000200022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and geographical differentiation of cultivated six-rowed naked barley landraces from the Qinghai-Tibet plateau of China detected by SSR analysis

Abstract: Cultivated six-rowed naked barley (Hordeum vulgare ssp. hexastichon var. nudum Hsü) is the oldest cultivated barley in China. We used 35 simple sequence repeat (SSR) markers selected from seven barley linkage groups to study the genetic diversity, geographical differentiation and evolutionary relationships among 65 H. vulgare ssp. hexastichon landrace accessions collected from the Qinghai-Tibet plateau of China, 25 accessions from Tibet (TB), 20 from Qinghai (QH) and 20 from Ganzi (GZ) prefecture in Sichuan pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…Previous population genetic studies have found that wild barley in Qinghai-Tibet plateau of China is a rich source of genetic diversity Feng et al 2006). The results of our survey showed that Tibetan wild barley displayed the highest Shannon diversity index value (0.5254) and the highest value of gene diversity (0.3286), indicating a higher genetic diversity than other barley sub-populations.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous population genetic studies have found that wild barley in Qinghai-Tibet plateau of China is a rich source of genetic diversity Feng et al 2006). The results of our survey showed that Tibetan wild barley displayed the highest Shannon diversity index value (0.5254) and the highest value of gene diversity (0.3286), indicating a higher genetic diversity than other barley sub-populations.…”
Section: Discussionmentioning
confidence: 52%
“…Barley can be grown in a wide range of environments such as the Arctic, high mountains and desert oases (Harlan 1976). It was suggested that worldwide cultivated barley originated from either the Fertile Crescent (Ancient Egypt, the Levant and Mesopotamia) (Harlan 1976), or the Qinghai-Tibet plateau region in China (Vavilov 1926;Brücher and Å berg 1950;Feng et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's used for animal feed, brewing malts, and human consumption Brown 1992). Considered as a model species for genetic analysis thanks to its widely available genetic information , an extensive amount of data has been produced from genetic diversity surveys of molecular marker loci in wild and cultivated barleys at national, regional and worldwide levels during the past decade (Orabi et al 2007;Pandey et al 2006;Brantestam et al 2006; Italic values indicate regional totals GTTTCTT 1 , Addition to the 5 0 -end of reverse primer; PCR*, Code of PCR condition detailed in Table 3; Chr 2 , Chromosome; g Genic marker Malysheva-Otto et al 2006;Feng et al 2006;Chabane et al 2005;Hou et al 2005;Hamza et al 2004;Baek et al 2003;Matus and Hayes 2002;Struss and Plieske 1998;Will iam et al 1997). Microsatellites or simple sequence repeats (SSRs) are highly variable markers that are commonly used in population genetic studies for the analysis of gene flow, parentage analysis, and studies on genetic diversity (Pfeiffer et al 1997;Streiff et al 1998;Jones and Ardren 2003).…”
Section: Introductionmentioning
confidence: 99%
“…All these traits together have probably resulted in its presently high level of genetic diversity at the species level. Moreover, many researchers have considered that habitat fragmentation, location, and population size have high impact on genetic diversity within populations (Feng et al, 2006;Arunkumar et al, 2012;Liu et al, 2013;Ghaffari et al, 2014). In the present study, the desert steppe group (PA, PB) exhibits a higher degree of genetic diversity than the typical steppe group (PC, PD, PE, and PF), This result was consistent with population size, suggesting that fragmented habitats, migration (decreased or absent) between populations, and genetic drift have probably contributed to the loss of diversity in the populations, especially in PF.…”
Section: Genetic Diversitymentioning
confidence: 99%